2012
DOI: 10.1097/pts.0b013e31823d0661
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of Pharmacology Teaching in Undergraduate Medical Students

Abstract: Our study shows that knowledge on pharmacology is incomplete in a large proportion of second-year medical students and indicates that there is an urgent need to review undergraduate training in pharmacology. The lack of relationship between the subjective ratings of teacher effectiveness and objective exam scores suggests the use of more demanding measures to assess the effectiveness of teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…in 2012 conducted a study to measure the effectiveness of pharmacology teaching in undergraduate medical students and found that there was an urgent need to review undergraduate training in pharmacology. [1] Pilot surveys conducted among interns by Jaykaran et al . and Akat et al .…”
Section: Introductionmentioning
confidence: 99%
“…in 2012 conducted a study to measure the effectiveness of pharmacology teaching in undergraduate medical students and found that there was an urgent need to review undergraduate training in pharmacology. [1] Pilot surveys conducted among interns by Jaykaran et al . and Akat et al .…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross-sectional study across fifteen European countries reported that medical students who had taken Pharmacology that focused on problem-based learning or mixed teaching methodologies developed better prescribing abilities, had greater knowledge of drugs and pharmacokinetics, and chose better therapeutics, which are essential competences of successful graduating medical students (Brinkman et al, 2016). It is very important to recognize the thorough knowledge of the fundamentals underpinning the rational use of drugs as a prerequisite for the adequate use of them in clinical settings (Urrutia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, correct prescribing of medicines today requires a complete knowledge of the pharmacokinetics, pharmacodynamics, drug–drug interactions, and other aspects of the agent to be prescribed. Unfortunately, there is abundant evidence in the form of prescription errors (paper and electronic) and increasing numbers of hospital admissions for drug toxicity in this country and many others that prescribers are not always sufficiently educated to properly administer and monitor present‐day therapeutics. For physicians, nurses, and physician assistants, the lack of sufficient clinical pharmacologic training can often be traced all the way back to undergraduate school.…”
Section: The Problemmentioning
confidence: 99%
“…Consequently, some medical schools have terminated pharmacology courses entirely and have gone solely to an organ‐based curriculum. Published studies have reported that undergraduate medical and nursing pharmacology training in other countries is insufficient as well.…”
Section: How Big Is the Problem?mentioning
confidence: 99%